2011
DOI: 10.1037/a0024944
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the adult attention-deficit hyperactivity disorder endophenotype: Parametric measurement of attention.

Abstract: Attention deficit hyperactivity disorder (ADHD) persists frequently into adulthood. The decomposition of endophenotypes by means of experimental neuro-cognitive assessment has the potential to improve diagnostic assessment, evaluation of treatment response, and disentanglement of genetic and environmental influences. We assessed four parameters of attentional capacity and selectivity derived from simple psychophysical tasks (verbal report of briefly presented letter displays) and based on a "theory of visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 87 publications
0
35
5
Order By: Relevance
“…This assumption is at least partly supported by the results of Finke et al . (), who found processing speed to be normal in an adult ADHD sample when DD was used as exclusion criterion. Further TVA‐based investigations (with larger groups of participants) specifically designed to examine the influences of DD, ADHD, and comorbidity would be required to shed light on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is at least partly supported by the results of Finke et al . (), who found processing speed to be normal in an adult ADHD sample when DD was used as exclusion criterion. Further TVA‐based investigations (with larger groups of participants) specifically designed to examine the influences of DD, ADHD, and comorbidity would be required to shed light on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of TVA and the related assessment tools have already been proved in various contexts. Thus, they were applied in a number of studies to systematically characterize specific groups of younger and older adult patients (e.g., Bublak et al, 2005Bublak et al, , 2011Bublak, Redel, & Finke, 2006;Duncan et al, 1999;Finke et al, 2011;Finke, Bublak, Dose, Müller, & Schneider, 2006;Habekost & Bundesen, 2003;Habekost & Starrfelt, 2009;Redel et al, 2012). Furthermore, it has been shown that the TVA attention capacity parameters react differently to enhancing manipulations, such as alertness cueing (Finke et al, 2012;Matthias et al, 2009), increase of temporal expectancy (Vangkilde, Coull, & Bundesen, 2012) and stimulating pharmacological interventions (Finke et al, 2011).…”
Section: Theory Of Visual Attention and Video Game Expertisementioning
confidence: 98%
“…Latent neurocognitive traits might, thus, constitute endophenotypes of ADHD that (i) differentiate between affected and unaffected individuals, (ii) are more closely related to the neurobiological changes associated with adult ADHD than the overt symptoms, and (iii) might provide specific information about target functions for interventions (11). In this regard, various attention tasks have been used to study ADHD, with the general finding being that children and adults with ADHD exhibit slowed response times (RTs) FOOTNOTE 1 (except for the most basic response tasks, [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%